Efficacy of selected rhizobacterial isolates for biocontrol of Rhizoctonia solani and growth promotion of maize in South Africa - Aveling, Terry A.S. (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2014.